GAG Protein of Arabidopsis thaliana LTR Retrotransposon Forms Retrosome-like Cytoplasmic Granules and Activates Stress Response Genes - Alexander Polkhovskiy; Roman Komakhin; Ilya Kirov (Plants, 2025)
LTR retrotransposons are widespread genomic elements that significantly impact genome structure and function. In Arabidopsis thaliana, the EVD LTR retrotransposon encodes a GAG protein essential for retrotransposon particle assembly. Here, we present a comprehensive analysis of the structural features, intracellular localization, and transcriptomic effects of the EVD GAG (evdGAG) protein. Using AlphaFold3, we identified canonical capsid (CA-NTD and CA-CTD) and nucleocapsid (NC) domains, with predicted disordered regions likely facilitating oligomerization. Transient expression of GFP-tagged evdGAG in protoplasts of A. thaliana and distant plant species (Nicotiana benthamiana and Helianthus annuus) revealed the formation of multiple large cytoplasmic aggregates resembling retrosomes, often localized near the nucleus. Stable overexpression of evdGAG in wild-type and ddm1 mutant backgrounds induced significant transcriptomic changes, including up-regulation of stress response and defense-related genes and downregulation of photosynthesis and chloroplast-associated pathways. Importantly, genes linked to stress granule formation were also up-regulated, suggesting a role for evdGAG in modulating cellular stress responses. Our findings provide novel insights into the cellular and molecular properties of plant retrotransposon GAG proteins and their influence on host gene expression.